Telaah Kritis Konsep Keagenan dalam Tinjauan Perspektif Islam Emansipatoris - Nurul Jihan Hasril; Alimuddin Alimuddin; Rahmawati HS (Accounting Department, Faculty of Economics and Business, Universitas Hasanuddin, 2024)
This research critically examines the agency theory through an Islamic lens. It adopts literature review approach, citing relevant and significant sources. The objective is to establish a conceptual framework for understanding agency conflicts. The findings indicate a fundamental divergence between Islamic principles and conventional agency concepts. Drawing on an emancipatory Islamic perspective, the research introduces the concept of Islamic agency, which upholds ethical considerations while acknowledging the prevailing social system. This study contributes to the ongoing discourse on agency theory by offering an alternative perspective rooted in Islamic principles and values. Further research is encouraged to explore the practical implications and potential applications of Islamic agency within organizational contexts.